PENGARUH METODE TUTOR SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR OPERASI HITUNG CAMPURAN - ma'sum, Muhammad asrori; Humairoh, Zuni; Yasmin, Faridah (LP2M STAI Darul Kamal NW Kembang Kerang, 2023)
Quantitative research is research used to analyze problems based on existing data to find causal relationships in a study. The purpose of quantitative research in this study is to determine the effect of the application of peer tutor method (Peer Teaching) to the learning outcomes of MI Madinatul Ulum students, especially on the material of mixed arithmetic operations. Peer tutor method (Peer Teaching) is one of the good methods to apply to the subject of mathematics. This method is believed to be able to provide solutions to the problems of students who are less able to understand the explanation presented by the teacher in mathematics learning activities. In this study the research method used is quasy experimental method with design nonequivalent control group design in the case of a two-step approach, the two-step approach is used to compare the two-step approach before and after the treatment (treatment). Based on research that has been done on the students of Class VI MI Madinatul Ulum on the material of mixed arithmetic operations where Class VI A as a control class and Class VI B as an experimental class, it has been found an increase in student learning outcomes by 17% in the experimental class. The percentage is known to be higher than that of the control class. This is evidenced using statistical tests that show that t count > ttable that is 4.08 > 1.68 for a significant level of 95%, so the initial hypothesis can be accepted. Based on the data obtained, the number of significant graduation between the control class and the experimental class, namely 17 experimental class students with a percentage of 68% passed KKM, while the control class counted only 4 students who passed KKM with a percentage of 16%.